THE EFFECTIVENESS OF BENSON’S RELAXATION THERAPY TO DECREASE THE LEVEL OF INSOMNIA ON CHRONIC KIDNEY DISEASE PATIENTS UNDERGOING HEMODIALYSIS - Dwi Retno Sulistyaningsih; Erna Melastuti (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2016)
AbstractAlmost 50 – 80 % patients with chronic kidney disease undergoing hemodialysis were reported to sleep disorder.  Insomnia is the highest prevalence  sleep disorder in the dialysis patients. This study aims to determine the effectiveness of Benson’s relaxation of the level of patients’ insomnia with chronic kidney disease in dyalisis patients. The design of this study is quasi-experimental with pretest-posttest design with control group. Fourty-two hemodyalisis patiens were recruited purposively from the hemodyalisis Islamic Hospital, Sultan Agung , Semarang. The sample was divided into two groups (treatment and control). Patients in the treatment group received Benson’s relaxation techniques during hemodialysis for 4 weeks and the control group received routine care. The insomnia severity index was used to measure  insomnia level. The result showed that there was significantly different score of insomnia level before and after relaxation Benson in the treatment group (p = 0.000). This study found that relaxation Benson seemed to be effective in decreasing the level of insomnia on chronic kidney disease patients undergoing hemodyalisis. Key words: Benson relaxation, insomnia, hemodialysis, chronic kidney disease